2013
DOI: 10.4028/www.scientific.net/amr.723.678
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Different Types of Permeable Pavement Utilization on Air Temperature above the Pavement

Abstract: This study investigate permeable pavement utilization and its impact on air temperature by using site measurement, statistical analysis, and Computational Fluid Dynamics (CFD) simulation. National Central University (NCU) main library is the case study for the simulations. Simulations on five pavement types (dense grade asphalt concrete/DGAC, permeable asphalt concrete/PAC, concrete, permeable interlocking concrete block/PICB, and grass block) shows that grass block and PICB can reduce air temperature, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…According to Yang, F. and Chen (2016), surface material imperviousness is an effective indicator to classify the ability of the land cover to absorb solar radiation. Pervious pavement has also been discovered to have a positive effect on outdoor thermal comfort Lin, J. D. et al (2013). Moreover, Irmak, Irmak, Yilmaz, and Dursun (2017) and Schrijvers et al (2016) showed the significant influence of surface albedo.…”
Section: Elements Of An Outdoor Thermal Environmentmentioning
confidence: 97%
“…According to Yang, F. and Chen (2016), surface material imperviousness is an effective indicator to classify the ability of the land cover to absorb solar radiation. Pervious pavement has also been discovered to have a positive effect on outdoor thermal comfort Lin, J. D. et al (2013). Moreover, Irmak, Irmak, Yilmaz, and Dursun (2017) and Schrijvers et al (2016) showed the significant influence of surface albedo.…”
Section: Elements Of An Outdoor Thermal Environmentmentioning
confidence: 97%
“…In the ENVI-met Database Manager (DBManager), a new soil profile consisting of different soil and surface materials was 130 parameterized to represent GGPs. Typical GGPs consist of 8 cm thick concrete stones (HOFFMANN & GEISSLER, 2022;HUNT & COLLINS, 2008;ICPI, 2020;LIN et al, 2013;STARKE et al, 2011). A soil profile of GGPs according to Figure 1 is implemented in ENVI-met.…”
Section: Parameterization Of Grass Grid Paversmentioning
confidence: 99%
“…Permeable pavements also affect the atmospheric phase (evaporation) of water. They lower not only the surface temperature of the pavement by 6.7-9.4°C but also the ambient temperature by 0.2-1.8°C, which contributes to the reduction of the phenomenon called an urban heat island (Lin et al 2013;Liu et al 2018).…”
Section: Permeable Pavementsmentioning
confidence: 99%